Interpreting images of nature with the expressive means of ballet art - Xu Zhang (ХДАК, 2025)
As one of the oldest dance distance arts in human history, ballet is a dazzling gem in dance distance art. The origin of ballet can be traced back to the 17th century, with a history of more than 400 years. After hundreds of years of inheritance and development, today's ballet art has reached a new level of development. Ballet, also known as "European classical dance", is a traditional dance form that originated from European folk culture. The origin of ballet can be traced back to before the 17th century. Traditional ballet was only a form of dance performance limited to the royal palace aristocracy, after the 1620s Ballet began to spread and develop among the people on a large scale. This dance form has initially spread among European folk culture Because of its elegant dance movements The graceful dance posture is deeply loved by the people. Therefore, its spread among the people was also quite rapid, only half a century later Ballet, as a form of dance, has gained numerous enthusiasts on the European continent and its spread has spread throughout the entire continent.
qualification work for obtaining master’s degree in specialty 024 Choreography
Keywords: балетні вистави